2014
DOI: 10.3389/fpsyt.2014.00088
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Fear Associated Phenotypes as Robust, Translational Indices of Trauma-, Stressor-, and Anxiety-Related Behaviors

Abstract: Post-traumatic stress disorder (PTSD) is a heterogeneous disorder that affects individuals exposed to trauma (e.g., combat, interpersonal violence, and natural disasters). It is characterized by hyperarousal, intrusive reminders of the trauma, avoidance of trauma-related cues, and negative cognition and mood. This heterogeneity indicates the presence of multiple neurobiological mechanisms underlying the development and maintenance of PTSD. Fear conditioning is a robust, translational experimental paradigm that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 91 publications
4
68
2
Order By: Relevance
“…However, use of the terms fear learning, fear conditioning, fear-motivated learning, fear memory, and fear extinction has become so widespread that many readers interested in these subjects might well skip altogether an article whose title does not contain those words. So they will be used here as they are in most other recent accounts of the subject (95,98,115,116,182,294,296,299,378,403,421,462,463,468,475,501,524,653).…”
Section: B Fear-motivated Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, use of the terms fear learning, fear conditioning, fear-motivated learning, fear memory, and fear extinction has become so widespread that many readers interested in these subjects might well skip altogether an article whose title does not contain those words. So they will be used here as they are in most other recent accounts of the subject (95,98,115,116,182,294,296,299,378,403,421,462,463,468,475,501,524,653).…”
Section: B Fear-motivated Learningmentioning
confidence: 99%
“…It can be associated with neutral stimuli that may become CSs, such as a noise, a tone or a light, and become a form of conditioned fear (146,223). In humans it has become standard testing for anxiety related to fear and characteristically increases in patients suffering from fear disorders (PTSD among them) or with other disorders that increase their propensity to suffer fear (95,299,462,463,502).…”
Section: B Fear-motivated Learningmentioning
confidence: 99%
“…Fear conditioning, a behavioral paradigm in which the subject learns an association between a neutral stimulus and an aversive unconditioned stimulus akin to the associations formed during trauma, has been widely utilized as a transitional animal model to study the traumatic experience common for all anxiety disorders (Briscione, Jovanovic, & Norrholm, 2014). Previous studies have identified two types of fear memories: (1) hippocampus dependent (contextual and trace fear conditioning) and (2) hippocampus independent (cued fear conditioning; Clark & Squire, 1998; Logue, Paylor, & Wehner, 1997; McEchron, Bouwmeester, Tseng, Weiss, & Disterhoft, 1998; Phillips & LeDoux, 1992; Solomon, Vander Schaaf, Thompson, & Weisz, 1986).…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…Fear extinction has been widely utilized as a translational animal model for the exposure therapies used for anxiety disorders (Briscione et al, 2014; Myers & Davis, 2006; Quirk & Mueller, 2007). In humans, several studies have demonstrated that PTSD patients show impaired fear extinction (Blechert, Michael, Vriends, Margraf, & Wilhelm, 2007; Michael, Blechert, Vriends, Margraf, & Wilhelm, 2007; Milad et al, 2009) as well as difficulty learning safety discrimination, another form of inhibitory learning where the subjects are trained to differentiate between a safe versus dangerous cue or context (Jovanovic, Kazama, Bachevalier, & Davis, 2012; Jovanovic et al, 2010, 2009; Lissek et al, 2005; for a review, see Christianson et al, 2012).…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…Variations include examining responses to "contextual" versus discrete CS+ [to examine phasic versus sustained fear responses (Garfinkel et al 2014;Glenn et al 2014;Grillon et al 2006 The short answer is it depends on the measure. PTSD patients exhibit increased potentiated startle responses to discrete fear cues (Briscione et al 2014;Norrholm et al 2011) and contextual fear cues (Grillon et al 2009b); however, increased fear is not consistently detected using other behavioral or physiological measures such as self-report or skin conductance response (SCR) (Glover et al 2011;Milad et al 2008). This difference may be related to specific fear circuitry that is being probed by these behavioral measures, as startle reactivity is thought to reflect "automatic" fear conditioning processes that do not rely on contingency awareness, while SCR and self-report reflect fear processes that require contingency awareness (Jovanovic et al 2006;Tabbert et al 2006).…”
Section: Fear Conditioning and Cued Recallmentioning
confidence: 99%